Murder lo mein - Chien, Vivien (Chien, Vivien. Noodle shop mystery., 2019)
"Lana Lee's stake in her family's Chinese restaurant is higher than ever now that she's been made manager. So when she enters Ho-Lee into Cleveland's Best Noodle Contest, Lana makes it her business to win--at all costs. But when a local food critic receives a threatening note in a fortune cookie and is later found dead, face-down in a bowl of lo mein, all bets are off... Now, along with her sweet-and-sour boyfriend Detective Adam Trudeau, Lana decides to take matters into her own hands and dig into the lives of everyone involved in the contest. But when she receives an ill-fated fortune, Lana realizes that in order to save the reputation of her restaurant, she needs to save herself first..."--Amazon.com.